Feminist social thought : a reader - Meyers,Diana Tietjens (Editor) (Routledge, 1997)
The commitment to gender equity that feminists have brought to philosophy has enabled feminists both to repudiate the sexist assumptions undergirding major philosophical traditions, and to make distinctive and important contributions to the field. Bringing together key articles in feminist ethics and social-political theory, this important collection highlights prominent concerns in contemporary feminist scholarship and the advances that feminist philosophers have made.